Emotional Intelligence in kindergarten and its relationship with some variables (Journal of the College of Education for Women, 2019)
This study aims at finding out the sentimental smartness of the kindergarten childrenand its relationship with some variables.1- The level of the sentimental smartness of the kindergarten children.2- Investigating the Zero hypothesis in that there are no significant statistical differences inthe sentimental smartness between the kindergarten children according to the sex variables(males and females).Some statistical tools have been used in order to arrive at the results that verify thehypotheses of this study. The researcher uses (1) the distinctive power between twodistinctive groups; (2) the relationship between the item and the total degree (Pearsoncorrelation factor); and (3) Elfakronbach formula to find out the stability of the measurementby the inner method.In order to investigate the verification of the zero hypothesis, the researcher uses the ttestto two in dependent samples. The results analysis shows that the calculated t is (0.884),which is less than the scheduled t, which is (1.96) at the level 0.05, and the degree of freedomis (198).